Real-time simulation for performance evaluation of bidirectional quasi z-source inverter based medium voltage drives. Issue 3 (3rd May 2016) - Prasad, Hanuman; Maity, Tanmoy
Abstract : Purpose: – The purpose of this paper is to present the performance of medium voltage induction motor drive fed through a bidirectional quasi z-source inverter (BQ-ZSI). By controlling the shoot-through duty ratio, BQ-ZSI is able to produce desired stable AC output voltage even during the situation of critical power supply variation. BQ-ZSI based drive has unique properties like boosting the output voltage during voltage sag, reducing harmonic distortion and improving the input power factor. Generally, adjustable speed drives are interrupted due to voltage sag in input supply that causes manufacturing and commercial losses. Replacing the conventional converter with BQ-ZSI, it can eliminate those common operational constraints. Design/methodology/approach: – This purpose is validated through simulations using real-time digital simulator (RTDS). RTDS is based on FPGA that interfaces the digital and analog inputs and outputs ports of the external hardware device. The IGBT based BQ-ZSI closed loop induction motor drive is modelled in SIMULINK and analysed through state space averaging technique. The suitable controllers are assigned and implemented on FPGA. The performance of the whole system is executed by offline simulation and analysed in hardware-in-loop (HIL) real-time simulator with fixed-time step. HIL simulation plays important role in design and development stage for BQ-ZSI based medium voltage drives where virtual plant is executed instead of physical plant. Findings: – Real-time simulation results show the performance of 225 KW, 3.3 KV induction motor for BQ-ZSI based motor drive under both steady state and dynamic conditions. The applied closed loop control method provides nearly zero steady state speed error at any operating frequency. Originality/value: – The application of BQ-ZSI is explored for medium voltage drive to solve the issues of power supply quality through the design of suitable control solution. Performance results presented in this paper can help in development of simple and low cost prototype controller for the drive.